Comparison of Five Prophylactically Intravenous Drugs in Preventing Opioid-Induced Cough: A Bayesian Network Meta-Analysis of Randomized Controlled Trials - Dong, Yunxia; Chang, Xiaohan (Frontiers in Pharmacology, 2021)
Background: Due to the absence of direct comparisons of different therapeutic drugs in preventing opioid-induced cough (OIC) during general anesthesia, clinicians often had difficulties in choosing the optimal drug for these patients. Hence, this network meta-analysis was conducted to solve this problem. Methods: Online databases including Pubmed, Embase, Web of Science, Cochrane database and Google Scholar were searched comprehensively to identify eligible randomized controlled trials (RCTs), up to March 15th, 2021. Within a Bayesian framework, network meta-analysis was performed by the “gemtc” version 0.8.2 package of R-3.4.0 software and pooled risk ratio (RR) associated with 95% credible interval (CrI) was calculated. Results: A total of 20 RCTs were finally enrolled and the overall heterogeneity for this study was low to moderate. Traditional pair-wise meta-analysis Results indicated that all of the five drugs (lidocaine, ketamine, dezocine, butorphanol and dexmedetomidine) could prevent OIC for four clinical outcomes, compared with placebo (all P<0.05). Moreover, dezocine had the best effect, compared with other drugs (all P<0.05). Network meta-analysis results suggested that the top three rank probabilities for four clinical outcomes from best to worst were dezocine, butorphanol and ketamine, based on individual/cumulative rank plots and surface under the cumulative ranking curve (SUCRA) probabilities. Node-splitting method indicated the consistency of the direct and indirect evidence. Conclusions: Our results indicated that all of these five drugs could prevent OIC compared with placebo. Moreover, the top three rank probabilities for four clinical outcomes from best to worst were dezocine, butorphanol and ketamine. Our results were anticipated to provide references for guiding clinical work and further high-quality RCTs were required to verify our findings.